Recombinant protein production in Pichia pastoris: from transcriptionally redesigned strains to bioprocess optimization and metabolic modelling. Issue 7 (10th November 2021) - Ergün, Burcu Gündüz; Berrios, Julio; Binay, Barış; Fickers, Patrick
ABSTRACT: Pichia pastoris is one of the most widely used host for the production of recombinant proteins. Expression systems that rely mostly on promoters from genes encoding alcohol oxidase 1 or glyceraldehyde-3-phosphate dehydrogenase have been developed together with related bioreactor operation strategies based on carbon sources such as methanol, glycerol, or glucose. Although, these processes are relatively efficient and easy to use, there have been notable improvements over the last twenty years to better control gene expression from these promoters and their engineered variants. Methanol-free and more efficient protein production platforms have been developed by engineering promoters and transcription factors. The production window of P. pastoris has been also extended by using alternative feedstocks including ethanol, lactic acid, mannitol, sorbitol, sucrose, xylose, gluconate, formate or rhamnose. Herein, the specific aspects that are emerging as key parameters for recombinant protein synthesis are discussed. For this purpose, a holistic approach has been considered to scrutinize protein production processes from strain design to bioprocess optimization, particularly focusing on promoter engineering, transcriptional circuitry redesign. This review also considers the optimization of bioprocess based on alternative carbon sources and derived co-feeding strategies. Optimization strategies for recombinant protein synthesis through metabolic modelling are also discussed. Abstract : The emerging P. pastoris strain and bioprocess designs, focusing on transcriptionally redesigned cells to enhance productivity or generate novel regulation mechanisms, and bioprocess optimizations with non-conventional carbon sources were evaluated.